2022
DOI: 10.3389/fimmu.2022.887602
|View full text |Cite
|
Sign up to set email alerts
|

Lnc90386 Sponges miR-33-5p to Mediate Mycoplasma gallisepticum-Induced Inflammation and Apoptosis in Chickens via the JNK Pathway

Abstract: Mycoplasma gallisepticum (MG) is one of the most important pathogens, that causes chronic respiratory disease (CRD) in chickens. Long non-coding RNAs (lncRNAs) are emerging as new regulators for many diseases and some lncRNAs can function as competing endogenous RNAs (ceRNAs) to regulate mRNAs by competitively binding to miRNAs. Here, we found that miR-33-5p was significantly up-regulated both in MG-infected chicken embryonic lungs and chicken embryo fibroblast cells (DF-1), and Lnc90386 negatively correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Specifically, we identified lnc90386 as a sponge for miR-33-5p, which weakens its inhibitory effect on JNK1. By doing so, lnc90386 defends against MG infection by inhibiting inflammation and apoptosis in DF-1 cells [21]. This finding highlights the importance of the lncRNA-mediated regulation of miRNA function in the context of MG infection.…”
Section: Mirnamentioning
confidence: 76%
See 1 more Smart Citation
“…Specifically, we identified lnc90386 as a sponge for miR-33-5p, which weakens its inhibitory effect on JNK1. By doing so, lnc90386 defends against MG infection by inhibiting inflammation and apoptosis in DF-1 cells [21]. This finding highlights the importance of the lncRNA-mediated regulation of miRNA function in the context of MG infection.…”
Section: Mirnamentioning
confidence: 76%
“…Exosomal miRNA sequencing data revealed that 30 miRNAs were significantly differentially expressed in the MG-infected group compared to the non-infected group [9]. Several of these miRNAs were selected for further study of their functions [9,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and this review section summarizes our research on the roles of miRNAs and exosomal miRNAs in regulating signaling pathways during MG infection in chickens (Figure 1, Table 1).…”
Section: Mirnas In Crdmentioning
confidence: 99%
“…MG-HS, a virulent strain, was isolated previously from a chicken farm in Hubei Province of China [ 32 ]. The concentration of viable Mycoplasmas in a suspension was then determined by a color-changing unit (CCU) assay that was reported in detail in our previous studies [ 33 ]. The concentration of MG-HS in this study was 10 9 CCU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some microRNAs promoted cell proliferation and attenuated the inflammatory response and apoptosis to resist M. gallisepticum infection. It was found that upon M. gallisepticum infection, Lnc90386 sponged miR-33-5p to negatively regulate the c-Jun N-terminal kinase (JNK) pathway and inhibited M. gallisepticum pMGA1.2 expression, promoting cell proliferation and inhibiting inflammatory damage and apoptosis caused by M. gallisepticum infection [ 98 ].…”
Section: Escape From Innate Immune Responsementioning
confidence: 99%